An Overview of Knowledge of Traditional Medicine Among Ponggalan Community, Giwangan, Umbulharjo, Yogyakarta - Rahmawati, Amanda Lista; Qarriy Aina Urfiyya (Science and Community Pharmacy Journal, 2023)
Abstract: Preface Traditional medicine is a material or natural ingredients used for traditional medicine. The use of traditional medicine in Indonesia is 49.5%, namely in the form of herbs. Many people use traditional medicine, but knowledge regarding the use of traditional medicine is still lacking. Many people in Ponggalan RW 05, Giwangan, Umbulharjo, Yogyakarta use traditional medicine, especially the elderly. Purpose : Knowing the description of the level of public knowledge about traditional medicine in Kampung Ponggalan RW 05, Giwangan, Umbulharjo, Yogyakarta.. Method : This research is a type of observational research that is descriptive in nature using a research instrument in the form of a questionnaire. Result : Description of the level of knowledge in Kampung Ponggalan RW 05, Giwangan Village, Umbulharjo District, Yogyakarta in January 2023 as many as 28 respondents (35%) with a good level of knowledge, as many as 42 respondents (53%) with a sufficient level of knowledge, and 10 respondents have a good level of knowledge less (13%). Conclusion : The level of knowledge of the Ponggalan community, Giwangan Village, Umbulharjo District, Yogyakarta about traditional medicine are sufficient.